Boosting inhibition performance of natural polyphenols for the prevention of calcium oxalate kidney stones through synergistic cooperativity - Si Li; Donghui Zhou; Zuoxuan Zhu; Xiaoyue Tan; Weiwei Tang; Junbo Gong (Communications Materials, 2023)
Abstract Binary drug combination usually targets different pathways to achieve cooperative therapy, but the exploitation of synergistic cooperativity between crystal growth modifiers that bind to the same site for preventing pathological biomineralization has yet to be realized. Here, we report that the binary inhibitor combinations of citrate with natural polyphenols can boost the inhibitory efficacy of calcium oxalate monohydrate crystallization, a primary component of kidney stones, up to four-fold greater than citrate alone. A combination of experimental and simulation techniques shows a strong synergy of four citrate-polyphenol inhibitor pairs on suppressing calcium oxalate monohydrate growth with minimal amounts of inhibitor, resulting from the reduction of growth kinetic constant paralleled with suppressing the crystallization driving force. Further, the inhibitor pairs demonstrated both in vitro and in vivo synergistic reductions of crystal-cell interactions, renal calcium oxalate deposition, and kidney injury, collectively presenting an effective therapeutic strategy for preventing calcium oxalate stones by boosting the inhibition efficacy of potent inhibitor pairs.